1980
DOI: 10.1159/000198482
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Intestinal Absorption of Iron by Sodium Alginate and Guar Gum in Rats

Abstract: Na-alginate as well as guar gum inhibit the absorption of a 59Fe-labelled iron dose (360 nmol) from tied-off jejunal segments of either normal or iron-deficient rats. In order to inhibit the absorption of the iron dose by half as compared with normal rats to which ionized iron was administered 1.2–8 mg of guar gum and 8–30 mg Na-alginate was necessary. In iron-deficient rats the highest dose of Na-alginate tested, 100 mg, inhibited the absorption of iron by about 20%; the highest dose of guar gum, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…These in vitro results are consistent with other findings. Wobling et al (1980) demonstrated that guar gum decreased iron absorption in tied-off jejunal segments of both normal and iron-deficient rats and decreased iron absorption, in vivo, in normal rats. Zemel and Zemel (1985) demonstrated that when guar gum (0.5%) was added to soy systems it significantly reduced iron solubility by 60.7% after undergoing a digestion with pepsin-HCl followed by the addition of bicarbonate, and digestion with pancreatin in the presence of bile extracts.…”
Section: Binding Characteristics Of Fiber Componentsmentioning
confidence: 92%
“…These in vitro results are consistent with other findings. Wobling et al (1980) demonstrated that guar gum decreased iron absorption in tied-off jejunal segments of both normal and iron-deficient rats and decreased iron absorption, in vivo, in normal rats. Zemel and Zemel (1985) demonstrated that when guar gum (0.5%) was added to soy systems it significantly reduced iron solubility by 60.7% after undergoing a digestion with pepsin-HCl followed by the addition of bicarbonate, and digestion with pancreatin in the presence of bile extracts.…”
Section: Binding Characteristics Of Fiber Componentsmentioning
confidence: 92%
“…Wölbling et al. () studied in situ the effect of sodium alginate in the absorption of 59 Fe‐labelled iron in tied‐off jejunal segments of normal or iron‐deficient anesthetised female Wistar rats. Tied‐off jejunal segments were filled with 2 mL of a solution containing 360 nmol 59 Fe‐labelled ferric chloride (pH 2) and increasing amounts of 1.2, 8, 30 and 100 mg of sodium alginate.…”
Section: Assessmentmentioning
confidence: 99%
“…The possible range of alginate compositions is huge due to the diversity in polymer length and G:M chemical composition [31,32]. How these compositional differences affect iron-binding potential and subsequent in vitro and in vivo cellular iron modulation is unknown, with previously published reports being inconsistent in their findings [14,[33][34][35]. This inconsistency is likely due to the fact that chemically different alginates were used throughout these studies, and data presented in this study demonstrate the dependence of iron chelation bioactivity on alginate chemical composition.…”
Section: Discussionmentioning
confidence: 99%